Home range use by Southern Ground-Hornbills (Bucorvus leadbeateri) - quantifying seasonal habitat selection and vegetation characteristics - Wyness, William (Percy FitzPatrick Institute of African Ornithology, 2017)
The habitat of an animal is extremely important as it provides that animal with the necessary resources for fulfilling its life-history requirements (Brennan & Block, 1993; Beyer et al. 2010). A habitat is defined as a region in environmental space which comprises of multiple abiotic and biotic variables influencing an animal's location (Krausman, 1999; Beyer et al. 2010). Animals tend to utilise discrete areas within a habitat, constituting part of their home range. Home range analysis helps to delineate the area used by an animal habitually and areas of concentrated use (Samuel et al. 1985; Seaman & Powell, 1996; Moorcroft et al. 1999; Mitchell, 2007; Rodgers & Kie, 2011). Patterns of differential use of space within an animal's home range are the result of competing demands and trade-offs. In this study, a kernel technique was used to determine the home range of four satellitetracked groups of Southern Ground-Hornbills Bucorvus leadbeateri in the Associated Private Nature Reserves (APNR) in the South African lowveld. Satellite data were analysed in ArcGIS® 9.3 to quantify habitat selectivity by groups of ground-hornbills at different times of the year to determine a) favoured habitat types, and b) the resolution with which they perceive their environment. Each of the I groups showed variation in the utilisation and extent of their home ranges on a seasonal basis. Home range sizes contracted towards the nest during the summer breeding season (December to March) and expanded during the dry season (April to September). Within the home range of one of the groups the physical characteristics of habitat types (i.e. vegetation types) were sampled at 250 random co-ordinates in order to assess whether habitat preference at the meso-scale can be explained by the physical attributes of that vegetation type. By profiling and quantifying the vegetation of areas in the home range that are used by Southern Ground-Hornbills to differing degrees, this information could be used as a proxy to facilitate re-introduction efforts, by providing a tool to identify optimal landscape configurations.